Influence of compost and canal clay scouring on sandy soil properties and wheat productivity under Irrigation water regime - Sayed Abdeen; Mahmoud EL-Sayed (International Journal of Recycling of Organic Waste in Agriculture)
Purpose Improving physio-chemical properties under irrigation regime by using natural conditioners to achieve the highest possible crop yield and water productivity.Method  A field experiment was conducted in a split-plot design with three replicates by addition of canal clay scouring (CS) and compost (CO) during two consecutive growing winter seasons of 2018/19 and 2019/20. The treatments were: control (100% and75% of water requirements), 20 and 40 (ton. ha-1) of CO and 40 and 80 (ton. ha-1) of CS as alone or mixed with each other under drip irrigation.Results The results showed that soil organic matter and cation exchange capacity increased by increasing the application rates of CO and CS. The lowest values of bulk and hydraulic conductivity were observed at 80 ton. ha-1 CS +40 ton. ha-1 CO. Also, field capacity, wilting point and available water were 20.94,5.97 and5.07%, respectively. The lowest values of ETa were observed at 80 ton. ha-1 CS +40 ton. ha-1 CO under 75% water irrigation requirement in all growth stages. The highest rates of the studied materials as a mixture gave a significant increase in nitrogen, phosphorus and potassium contents of grains and straw of wheat crop. The highest yield of straw and grain were 9523.81 and 6428.57 kg ha-1, respectively. Also, it could be observed that the highest percentage of CWP and IWP were 21.05 and 14.53%, respectively, under 75% irrigation water requirement.Conclusion Application of clay and compost can improve soil physio-chemical properties, water productivity and crop yield under irrigation water regime.